PELATIHAN PENGGUNAAN KOMPUTER DAN SIMULASI KEGIATAN ANBK PADA SISWA SISWI SDN 02 CIHERANG - Edang, Ignasius Alfon Hanjuk; Hardjo, Ayra Diputera; Effendi, Absarani Maharani; Rajasa, Daud Angga; Arisandi, Desi (Jurnal Serina Abdimas, 2023)
The era of globalization has propelled the use of computer devices as an integral part of daily human life. The Ministry of Education and Culture responds to this change by integrating the Computer-Based National Assessment Program (ANBK) into school activities. ANBK aims to measure basic and specific competencies of students according to the curriculum, including literacy, numeracy, and skills in critical thinking, creativity, collaboration, and communication. Primary School Negeri 02 Ciherang involves fifth-grade students in ANBK, but challenges arise as most students have not mastered computer usage. Students from Group 2 of the Thematic Real Work Lecture (KKN-T) initiative participate by organizing computer usage training and ANBK problem simulations. The training covers literacy and numeracy questions, computer operation, and direct simulation of ANBK problems using computers. Over three weeks, the training takes place twice a week on Tuesdays and Thursdays. Gradual evaluations are conducted to identify challenges. In the first week, some students face difficulties, but progress is evident in the second week, where they can operate computers and complete ANBK simulations on time. In the third week, additional literacy and numeracy questions are introduced, involving all students. With the initiative of KKN-T students, the challenges are overcome, showing positive developments in computer proficiency, and preparing the students of SDN 02 Ciherang to confidently participate in ANBK ABSTRAK Era globalisasi mendorong penggunaan perangkat komputer sebagai bagian integral dari kehidupan sehari-hari manusia. Kementerian Pendidikan dan Kebudayaan merespons perubahan ini dengan mengintegrasikan Program Asesmen Nasional Berbasis Komputer (ANBK) ke dalam kegiatan sekolah. ANBK bertujuan mengukur kompetensi dasar dan khusus siswa sesuai kurikulum, termasuk literasi, numerasi, dan keterampilan berpikir kritis, kreatif, kolaboratif, serta komunikatif. Sekolah Dasar Negeri 02 Ciherang melibatkan siswa kelas 5 dalam ANBK, namun tantangan muncul karena sebagian besar siswa belum menguasai penggunaan komputer. Mahasiswa Kelompok 2 Kuliah Kerja Nyata Tematik (KKN-T) turut ambil bagian dengan menyelenggarakan pelatihan penggunaan komputer dan simulasi soal ANBK. Pelatihan mencakup soal literasi membaca dan numerasi, pengoperasian komputer, serta simulasi mengerjakan soal ANBK langsung menggunakan komputer. Selama tiga minggu, pelatihan dilaksanakan dua kali seminggu pada hari Selasa dan Kamis. Evaluasi bertahap dilakukan untuk mengidentifikasi kendala. Pada minggu pertama, beberapa siswa mengalami kesulitan, tetapi kemajuan terlihat pada minggu kedua, di mana mereka sudah mampu mengoperasikan komputer dan menyelesaikan simulasi ANBK tepat waktu. Pada minggu ketiga, tambahan soal literasi membaca dan numerasi diberikan, melibatkan seluruh siswa. Dengan inisiatif Mahasiswa KKN-T, siswa SDN 02 Ciherang berhasil mengatasi kendala awal, menunjukkan perkembangan positif dalam penguasaan komputer, dan mempersiapkan mereka untuk mengikuti ANBK dengan lebih percaya diri.